THE BUDGET OF MIXED LAYER SALINITY IN THE SOUTHEAST INDIAN OCEAN DURING LAST DECADE - Iskandar, Mochamad Riza (Marine Research in Indonesia, 2019)
The last decade of mixed layer salinity budget in the southeast Indian Ocean is evaluated by using monthly gridded Argo dataset from January 2004 to December 2015. The evaluation of salinity budget through the examination of evaporative, precipitation, Ekman advection, geostrophic advection and entrainment terms. The mixed layer salinity (MLS) in SETIO tend to fresher in 2004-2014 and slightly saltier again in 2015. The cycle of MLS closely follows the freshwater flux of atmospheric forcing. The Ekman and geostrophic advection are smaller than the atmospheric terms. Even though, the geostrophic advection tends to make MLS fresher. The vertical entrainment competes with the atmospheric flux to make saltier the MLS.